Effect of mode of anesthesia on radiation exposure in patients undergoing endovascular recanalization of anterior circulation embolic stroke - Hemmerich, Felix; Weyland, Charlotte S.; Schönenberger, Silvia; Ringleb, Peter A.; Möhlenbruch, Markus Alfred; Bendszus, Martin; Pfaff, Johannes (Journal of neuroInterventional surgery, 2019)
Purpose To determine the effect of general anesthesia (GA) versus conscious sedation (CS) on radiation exposure (RE), procedure time (PT), and fluoroscopy time (FT) in patients receiving endovascular stroke treatment (EST) for large vessel occlusions (LVOs) in the anterior circulation. - Methods Retrospective analysis of an institutional review board−approved prospective stroke database of a comprehensive stroke center focusing on RE (as dose area product (DAP) in Gy.cm², median (IQR)), PT, and FT (in minutes, median (IQR)) in patients receiving EST for LVOs of the anterior circulation according to the mode of anesthesia during the intervention. - Results Overall 544 patients were included in this analysis (GA: n=143, CS: n=401). For all included LVOs in the anterior circulation PTs (GA: 69 (44-100); CS: 59 (37-99); p=0.235), FTs (GA: 33 (20-56); CS: 29 (16-51); p=0.286), and RE (DAP, GA: 116.23 (73.47-173.41); CS: 110.5 (68.35-184.65); p=0.929) were comparable. In a subgroup analysis of occlusions of the middle cerebral artery (M1-segment; GA: n=80/544, 14.7%; CS: n=211/544, 38.8%), PTs (GA: 69 (37-101); CS: 54 (35 - 89); p=0.223), FTs (GA: 33 (19-55); CS: 25 (14-48); p=0.264), and RE (DAP, GA: 110.91 (66.8-169.12); CS: 103.8 (63.17-181); p=0.893) were similar. - Conclusion In this retrospective analysis, no effect of the mode of anesthesia on the radiation exposure during EST was detected as GA and CS showed comparable PT, FT, and DAPs.